Phytochemical analysis and antibacterial activity of Staurogyne sp. in fish disease bacteria - Nugraha, Media Fitri Isma; Novita, Hessy; Rajamuddin, Muh Alias; Yunita, Rossa; Enggarini, Wening; Reflinur, Reflinur; Maharani, Fasya Hadaina; Elya, Berna (Torani Journal of Fisheries and Marine Science, 2019)
This study was aimed to identify the potential use of active compounds extracted from Staurogyne sp as an antibacterial agent to control disease-causing bacteria in fish. Staurogyne sp, an aquatic plant collected from Bantimurung, South Sulawesi were subjected to allelochemical compound. Plant extracts were tested to five bacteria including four types of bacterial pathogen, such as Aeromonas hydrophilla, Edwardsiella ictaluri, Streptococcus agalactiae, and Flavobacterium columnare, and one bacterial sensing quoroum, Chromobacterium violaceum. Based on phytochemical analysis, Staurogyne’s extracts derived from both stem and root contained flavonoids, phenols, and antioxidants compounds with the concentration of 0.018 mgQE/g, 0.3471 mgGAE/g, and  1004,391 IC50 µg/mL, respectively. In addition, Staurogyne plant extracts derived from both their stem and root has also produced both saponins and glycosides compounds. Plant extracts derived from Staurogyne’s leaves revealed three major chemical compounds such as flavonoids (0.77 mgQE/g), phenol (0.0629 mgGAE/g), and glycosides (+). However, no antioxidants and saponin compounds were detected.  Applying plant extracts as an antibacterial on five disease-causing bacteria causing diseases in aquaculture, such as Aeromonas Hydrophilla, Edwardsiella ictaluri, Streptococcus agalactiae, Flavobacterium columnare, and Chromobacterium violaceum bacterials revealed that at concentration of 0.1 g the Staurogyne sp extracts did not influence all the bacterials growth. However, by application of plant extract at concentration of 0.2 g on the growth media,three out of 5 tested bacterials (Aeromonas hydrophilla, Edwardsiella ictaluri, and Streptococcus agalactiae) showed intermediate inhibition responses on bacterial growth. The growth of remaining two bacterials pathogen, Flavobacterium columnare and Chromobacterium violaceum at 0.2 g plant extract of Staurogyne sp was not affected. This study revealed that the use of active compound derived from Staurogyne sp would be potential to be used in inhibiting disease-causing bacterial in fish in future. However, optimum concentration of the plant extracts, in particular on the inhibition of the growth of disease-causing bacteria in fish is still needed to adjust.Key words: Antibacterial, aquatic plant, Staurogyne sp, fish disease